The «catalogo della cooperazione»: the road for a relaunch of the National library service - Turbanti, Simona (Bibliothecae.it, 2016)
The meeting for the thirty-year anniversary of Servizio bibliotecario nazionale (SBN) was held on April 1st in the National Central Library of Rome. Several aspects of the major Italian network of libraries were discussed in the seminar; the article would like to be a way of sharing some ideas about ‘SBN system’ and for his relaunch.